Transmission line fault identification and classification with integrated FACTS device using multiresolution analysis and naïve bayes classifier - Elhadi Emhemed Aker; Mohammad Lutfi Othman; Ishak Aris; Noor Izzri Abdul Wahab; Hashim Hizam; Osaj Emmanuel (Institute of Advanced Engineering and Science, 2020)
This paper is present a novel approach for solving the pending under-reach problem encountered by distance relay protection scheme in the 3rd zones protection coverage for a midpoint STATCOM compensated transmission lines. The propose transmission line model is develop in Matlab for analyzed feature extraction using Discrete Wavelet multiresolution analysis approach. Extracted feature from standard deviation and entropy energy contents of SLG transient faults current at location beyond the integrated STATCOM used for machine learning algorithm model building using WEKA software. The Naïve Bayes classifier model perform best with robustness prediction and detection of faults with quick convergence even with less training data. The outperformance of the proposed classifier has been 100 % for the relay algorithm modification for under-reach problem elimination in 3rd zones protection coverage.